1998
DOI: 10.1002/(sici)1099-0968(199806)6:2<96::aid-erv236>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a day treatment programme for eating disorders

Abstract: A day hospital treatment programme is described for eating disordered patients who would otherwise require inpatient treatment. The characteristics at presentation of 106 consecutive patients are described. Of patients completing the programme, 65 could be recruited for the outcome study. At presentation, 26 per cent ful®lled DSM-IV criteria for anorexia nervosa, 65 per cent for bulimia nervosa and 9 per cent had an eating disorder not otherwise speci®ed. The average length of treatment of all patients was 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 13 publications
5
31
0
1
Order By: Relevance
“…DH treatment is typically associated with large improvements. After 16 weeks of treatment in The Treatment Center for Eating Disorders in Munich, Germany, body mass index (BMI) for patients with anorexia nervosa (AN) increased an average of 3 points and bingeing and vomiting were significantly reduced for BN patients (Fittig, Jacobi, Backmund, Gerlinghoff, & Wittchen, 2008;Gerlinghoff, Backmund, & Franzen, 1998). Improvements were generally maintained at 18-month follow-up and 51% of AN-restricting, 29% of AN-binge/purge and 40% of BN treatment completers were classified as being in remission at follow-up (Fittig et al, 2008).…”
mentioning
confidence: 99%
“…DH treatment is typically associated with large improvements. After 16 weeks of treatment in The Treatment Center for Eating Disorders in Munich, Germany, body mass index (BMI) for patients with anorexia nervosa (AN) increased an average of 3 points and bingeing and vomiting were significantly reduced for BN patients (Fittig, Jacobi, Backmund, Gerlinghoff, & Wittchen, 2008;Gerlinghoff, Backmund, & Franzen, 1998). Improvements were generally maintained at 18-month follow-up and 51% of AN-restricting, 29% of AN-binge/purge and 40% of BN treatment completers were classified as being in remission at follow-up (Fittig et al, 2008).…”
mentioning
confidence: 99%
“…The results showed that BMI increased or remained stable in the majority of patients which is in line with the significant improvements in BMI reported in comparable investigations (Gerlinghoff et al, 1998;Robinson, 2003). Furthermore, in all psychological measures and associated subscales, the majority were found to improve between admission and discharge, with more than three quarters of patients making improvements on the BDI score, SEDS total score and the anorexic dietary cognitions subscale.…”
Section: Discussionmentioning
confidence: 99%
“…Across both conditions, 63% of cases were classified as recovered. Gerlinghoff et al (1998) followed 65 patients out of 106 who had begun day treatment between 6 and 33 months earlier. Patients were primarily adults, diagnosed at baseline with AN, BN, and EDNOS.…”
Section: Partial Hospitalizationmentioning
confidence: 99%